(untitled) (Società e diritti, 2022)
Abstract This paper, written in memory Professor of Valerio Onida (1936-2022), ex-alumnus of Milan “Liceo Classico Carducci”, Professor of Constitutional Law at the University of Milan and President Emeritus of the Italian Constitutional Court, discusses the problem of homelessness. The Author deals in this contribution with an important but little known profile of the activity of Valerio Onida as a jurisconsult. In June 1993 he took care of the effectiveness of the rights of the subjects placed at the extreme margin of Italian society: the homeless. In this essay, in addition to offering a tribute to the high figure of man and jurist. In June 1993 Onida faced the problem of the effectiveness of the rights of the subjects placed at the extreme edge of Italian society: the homeless. In this essay, in addition to offering a tribute to the high figure of the man and the jurist, reveal the important and lengthy effects that a pro veritate opinion of Onida has had in our legal system and the human interweavings the relationship, the civil and social commitment and the socio-legal studies that underlie it.